Complement 3 (C3) within the hypothalamic arcuate nucleus is a potential key mediator of the effect of enhanced nutrition on reproductive development in young bull calves - Kate Keogh; Stephen Coen; Pat Lonergan; Sean Fair; David A Kenny (BMC Genomics)
Abstract Background Reproductive development may be advanced in bull calves through enhanced dietary intake during the early life period. This effect between enhanced nutrition with subsequent earlier reproductive development is orchestrated through signalling within the hypothalamic-pituitary-testicular axis. Within the hypothalamus, the arcuate nucleus (ARC) is crucial for the integration of peripheral metabolic status with subsequent gonadotropin releasing hormone (GnRH) signalling; however, the precise molecular control regulating this effect is not fully known. The aim of this study was to evaluate the global transcriptomic and proteomic responses to varied plane of nutrition during early calf-hood in young dairy bull calves. Additionally, we sought to integrate these ‘omics’ datasets to determine key genes and proteins contributing to earlier reproductive development. Between 2–12 weeks of age, 30 Holstein-Friesian bull calves (mean age: 17.5 days; mean bodyweight 48.8 kg), were offered either a high or moderate plane of nutrition with 15 calves in each group. At 12 weeks of age, all calves were euthanised and the ARC tissue isolated from each calf. The ARC tissue was then used for global transcriptomic (miRNAseq and mRNAseq) and proteomic analyses. Results Bioinformatic analyses were undertaken to determine differentially expressed transcripts (FDR < 0.1; fold change > 1.5) between the dietary treatment groups, resulting in the identification of 1 differentially expressed miRNA (miR-2419-3p) and 83 differentially expressed mRNA in the ARC region. mRNA target gene prediction identified Complement 3 (C3) as a target of miR-2419-3p, suggesting a relationship between the two transcripts. Furthermore, through a co-regulatory network analysis conducted on the proteomics dataset, C3 was revealed as a hub protein. Additionally, through the proteomic network analysis, C3 was interacting with proteins involved in both insulin and GnRH signalling, highlighting a potential role for C3 in mediated the effect of enhanced nutritional status with earlier reproductive development within the ARC. Conclusion This study highlights an effect of altered plane of nutrition in early life on the molecular control of the hypothalamic ARC. Additionally, results generated suggest a potential role for the C3 gene in mediating the interaction between enhanced metabolic status with reproductive development within the ARC, regulated by miR-2419-3p.